Conserving the Paraguay-Paraná Fluvial Corridor in the XXI Century: Conflicts, Threats, and Challenges - Baigún, Claudio Rafael M. (2021)
The Paraguay-Paraná river system represents a unique, free-flowing corridor that extends about 3500 km southwards from the Pantanal to the Rio de la Plata estuary, crossing four countries. The absence of fragmentation along the main channels and its still well-connected floodplains have preserved longitudinal and lateral functional and structural connectivity, defining critical ecological gradients for the biota and species life cycles. The lack of dams represents a noticeable feature that benefits migratory species supporting small-scale fisheries providing food security and the conservation of other ecosystem services with associated livelihoods. The ecological integrity of this corridor could be severely affected by the potential expansion of the Hidrovía Paraguay-Paraná for improving commercial trade, the foreseen installation of new dams in the Paraná basin, in addition to other current impacts and threats. Conservation of the corridor for societal benefits, involving the sustainable development of activities associated with the use of the fluvial territory, requires maintaining the natural ecological process that sustains livelihoods and biodiversity. This calls for innovative strategies encompassing water governance process, social and environmental information related to expected impacts, a better understanding of synergies between processes, and foremost an interdisciplinary approach to design and apply integrative and multi-scale management policies.